Civil Engineering and Sustainable Development - Agus Setyo Muntohar (Civil Engineering Department, Universitas Muhammadiyah Yogyakarta, 2021)
The field of civil engineering cannot be separated from the daily life of the people. The skyscrapers that can be seen everywhere, the thriving road traffic, the beautiful bridges and dams like sturdy fortresses, and tunnels and subsurface structures are an indispensable part of our lives. The global trend of sustainable development, Civil Engineering must eliminate or reduce environmental problems that may arise in the project. Starting from large-scale economic construction, so that development can provide benefits to mankind and make the environment get sustainable development and improvement. Therefore, the sustainable development of Civil Engineering is very worthy of discussion and study